OP13 Modified 2-stage vs. 3-stage ileal pouch-anal anastomosis result in equivalent long-term functional outcomes and pouch survival: A matched-pair analysis. (21st January 2022) - Holubar MD- MS, S; Prien, C; Jia, X; Liska, D; Kessler, H; Valente, M; Lightner, A; Gorgun, E; Hull, T; Steele, S
Abstract: Background: Long-term outcomes data after modified 2-stage ileal pouch anal anastomosis (IPAA), defined as completion proctectomy (CP) and IPAA without loop ileostomy, is lacking. We aimed to describe long-term functional results, patient satisfaction, and pouch survival in a cohort of patients from a high-volume center. We hypothesized selective m2-stage can result in comparable long-term pouch survival relative to a 3-stage approach. Methods: Our institutional ileal pouch database was retrospectively reviewed to identify patients who underwent index IPAA surgery from 1983–2019. Adults >18 years of age who underwent CP with IPAA were included. At our specialized institution, m2-stage is performed selectively based on surgeon judgement. Patients were stratified into 2 groups (3-stage vs m2-stage) and matched on a 1:1 basis based on age ±5, year of operation ±3, gender, preoperative diagnosis, double-stapled vs handsewn, and laparoscopy. Primary outcome was pouch survival, with pouch failure defined as permanent diversion, pouch excision, or conversion to a Kock pouch. Results: In total, 2, 433 patients were included, of whom 2, 198 (90.3%) underwent 3-stage IPAA and 235 (9.7%) m2-stage IPAA. Matching resulted in 223 matched pairs, and long-term pouch survival (95.5% vs 93.2%, p=0.32) did not significantly differ (Figure 1 ). Short-term outcomes in the matched pairs revealed a shorter postoperative length of stay in the 3-stage patients (5 vs 8 days, p<0.001), but no significant difference in postoperative complications (12.1% vs 17%, p=0.09) was seen between the matched 3-stage and m2-stage patients, respectively. Functionally, there was no difference in the number of stools/24 hours (7 vs 7, p=0.33) or in proportion of patients requiring seepage protection at night (29.7% vs 24.6%, p=0.31). However, 3-stage patients required significantly more seepage protection during the day (25.1% vs 15.0%, p=0.02). Regarding pouchitis, there was no difference in the proportion of patients reporting recent symptoms (33.4% vs 33.3%, p=1.0), episodes in the last year (0 vs 0, p=0.51), or pouchitis requiring continuous medication (16.7% vs 10.1%, p=0.10). Patient satisfaction was similar as no difference in the proportion of those who would have surgery again (90.4% vs 93.7%, p=0.34), those who would recommend surgery (94% vs 95.5%, p=0.68), or overall patient satisfaction with surgery on a scale of 1 – 10 (highest) (3 vs 7, p=0.07) was reported. Figure 1: Kaplan-Meier curve for pouch survival (matched pairs) Conclusion: Long-term outcomes were similar in patients who underwent modified 2-stage and 3-stage IPAA. Modified 2-stage IPAA is an alternative for selected patients with limited options if performed at high-volume centers in experienced hands.